2022
DOI: 10.2147/copd.s370540
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Adherence and Persistence of Single- and Multiple-Inhaler Triple Therapies Among Patients with Chronic Obstructive Pulmonary Disease in an English Real-World Primary Care Setting

Abstract: Purpose Triple therapy comprising a long-acting muscarinic antagonist, long-acting β 2 -agonist and inhaled corticosteroid is recommended for patients with chronic obstructive pulmonary disease (COPD) who continue to experience frequent exacerbations or symptoms whilst receiving dual therapy. Adherence and persistence to multiple-inhaler triple therapy (MITT) is known to be poor. This study assessed comparative adherence to single-inhaler triple therapy (SITT) versus MIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“… 21 These findings could also be explained by the effects of a reduction in adherence to triple therapy over longer time periods, as shown previously by Halpin et al . 6 However, further investigation is required as this study did not require patients to be continuously using FF/UMEC/VI post-switch, although the results of the sensitivity analysis (which required 6 months continual MITT use pre-switch and 6 months continual single-inhaler FF/UMEC/VI use post-switch) were similar to those for the overall cohort.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 21 These findings could also be explained by the effects of a reduction in adherence to triple therapy over longer time periods, as shown previously by Halpin et al . 6 However, further investigation is required as this study did not require patients to be continuously using FF/UMEC/VI post-switch, although the results of the sensitivity analysis (which required 6 months continual MITT use pre-switch and 6 months continual single-inhaler FF/UMEC/VI use post-switch) were similar to those for the overall cohort.…”
Section: Discussionmentioning
confidence: 84%
“… 5 Improved persistence to SITT has also been shown compared with MITT. 6 Despite these studies, real-world data on switching from MITT to SITT are lacking, and evaluations of healthcare resource use (HCRU) are limited. 7 …”
Section: Introductionmentioning
confidence: 99%
“… 23 The current GOLD strategy document includes recommendation that single inhalers may be more convenient and effective than multiple inhalers, 6 and prior studies have demonstrated that patients receiving single-inhaler triple therapy have significantly better adherence and persistence compared with patients receiving triple therapy via multiple inhalers. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the adherence results of this study are consistent with previous literature. 14 Lastly, one of the outcomes of interest in this study is adherence, as measured by PDC. There is a lack of consensus on the most appropriate adherence calculation when multiple medications are included in the line of therapy.…”
Section: Discussionmentioning
confidence: 99%